Numerical Investigation of the Dynamics of a Flexible Filament in the Wake of Cylinder. Issue 4 (August 2014) - Ru-Nan Hua,; Zhu, Luoding; Xi-Yun Lu,
Abstract: Fluid-structure-interaction problems are ubiquitous, complicated, and not yet well understood. In this paper we investigate the interaction of a leading rigid circular cylinder and a trailing compliant filament and analyze the dynamic responses of the filament in the wake of the cylinder. It is revealed that there exist two flapping states of the filament depending on the cylinder-filament separation distance and the relevant critical distance distinguishing the two states is associated with the Reynolds number and the filament length. It is also found that the drag coefficient of the cylinder is reduced but that of the filament may be increased or decreased depending on its length. Compared with a single filament in a uniform flow, the filament of the same mechanical properties flapping in the wake of the cylinder has a lower frequency and a greater amplitude.